The current and future incidence and mortality of gastric cancer in 185 countries, 2020–40: A population-based modelling study - Morgan, Eileen; Arnold, Melina; Camargo, M. Constanza; Gini, Andrea; Kunzmann, Andrew T.; Matsuda, Tomohiro; Meheus, Filip; Verhoeven, Rob H.A.; Vignat, Jérôme; Laversanne, Mathieu; Ferlay, Jacques; Soerjomataram, Isabelle (EClinicalMedicine, 2022)
To examine global patterns of gastric cancer in 2020 and the projected burden in 2040. Data on primary gastric cancer were extracted from the GLOBOCAN database for the year 2020. Age-standardized incidence and mortality rates were calculated by sex, country, world region and level of human development index (HDI) for 185 countries. The predicted burden of incidence and mortality in 2040 was calculated based on demographic projections. In total, ∼1.1 million new cases and 770,000 deaths of gastric cancer were estimated in 2020. Incidence rates were on average 2-fold higher in males than females (15.8 and 7.0 per 100,000, respectively) with variation across countries. Highest incidence rates were observed in Eastern Asia for both males and females (32.5 and 13.2, respectively); males residing in Japan (48.1), Mongolia (47.2) and Korea (39.7) had the highest rates in the world. Incidence was lowest in Africa with incidence rates < 5 per 100,000. Highest mortality rates were observed in Eastern Asia for both males (21.1) and females (8.8). A lower share of deaths was observed in very high HDI countries compared to medium and low HDI countries. The annual burden of gastric cancer is predicted to increase to ∼1.8 million new cases and ∼1.3 million deaths by 2040. These estimates of the global burden of gastric cancer pinpoint countries and regions of high incidence and mortality in need of cancer control initiatives. Primary prevention through eradication of H. pylori and behavioural changes such as reducing salt intake, smoking, obesity, and alcohol, remains key in stomach cancer control. No direct funding was received. All authors had access to the included study data and all authors agreed with the final decision to submit for publication.